If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(3x + 2) = 4 Reorder the terms: 9(2 + 3x) = 4 (2 * 9 + 3x * 9) = 4 (18 + 27x) = 4 Solving 18 + 27x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 27x = 4 + -18 Combine like terms: 18 + -18 = 0 0 + 27x = 4 + -18 27x = 4 + -18 Combine like terms: 4 + -18 = -14 27x = -14 Divide each side by '27'. x = -0.5185185185 Simplifying x = -0.5185185185
| 2(x+26)=264 | | 1(3/11-7d/12) | | 7w-3(w-2)=20 | | 1=1+4p-4p | | 100(x-3)-8= | | 3n+15=18n | | x^2-x-6=x^2-6x+9 | | Y=x^4+12x^2+36 | | 4(2y-1)=-4 | | 3(-12)+47+(-12)+26=27+(-12)+10 | | -10=16 | | 14x-3x=22 | | 5x+26=3(x+1)-2x | | 3+4a=10a+10 | | -9w-24=-3(w-6) | | 5n=10.40 | | 13=1-8n-4 | | 1/4k+3/4=5/6k-1 | | 24=24y | | -11c-35=4c-8 | | -2(4-x)=2-8 | | y=(-60)(1)+b | | 0.75p-1.25=0.333333p | | 3(x+5)=2(3x-4) | | 25=-h | | 4x+9x=292 | | n-35=25-4n | | 9(v+3)=3v-3 | | -17=-32-3/5y | | 8-8p=p | | (8a-9)(3a^2-2a-2)= | | -1/3(n+15)=6 |